PROTECTION AGAINST PLANT PESTS BASED ON RESISTANT WHEAT VARIETIES - Amirkulov Otabek Saidullaevich (Web of Journals Publishing, 2024)
This article explores various types of wheat contaminated with wheat juice in a plant protection laboratory. As a result, the durability of various wheat varieties was evaluated and relatively stable varieties were determined.
Keywords: sorghum, damage, pest, steady, wheat, steady, moderately resistant, insect, crop, grain, struggle, quality, efficiency, relative, productivity, growing, local, grain, seeds, ton, hectare, research, improvement.